2018
DOI: 10.1016/j.molp.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Sphingolipid Signaling in Plant Response to Biotic and Abiotic Stresses

Abstract: Plant sphingolipids are not only structural components of the plasma membrane and other endomembrane systems but also act as signaling molecules during biotic and abiotic stresses. However, the roles of sphingolipids in plant signal transduction in response to environmental cues are yet to be investigated in detail. In this review, we discuss the signaling roles of sphingolipid metabolites with a focus on plant sphingolipids. We also mention some microbial sphingolipids that initiate signals during their inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 120 publications
(193 reference statements)
0
70
0
Order By: Relevance
“…Sphingolipids can form membrane microdomain (lipid raft), which is a platform for the recruitment of signaling molecules. Lipid rafts can cooperate with cholesterol to provide conformational support for membrane proteins on the outer leaflet of the membrane, and are essential for cell membranes because the transmembrane signal transmission is amplified in this large platform . As a product of membrane lipid peroxidation, MDA content in tissues increases greatly under stress .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids can form membrane microdomain (lipid raft), which is a platform for the recruitment of signaling molecules. Lipid rafts can cooperate with cholesterol to provide conformational support for membrane proteins on the outer leaflet of the membrane, and are essential for cell membranes because the transmembrane signal transmission is amplified in this large platform . As a product of membrane lipid peroxidation, MDA content in tissues increases greatly under stress .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid rafts can cooperate with cholesterol to provide conformational support for membrane proteins on the outer leaflet of the membrane, and are essential for cell membranes because the transmembrane signal transmission is amplified in this large platform. 43,44 As a product of membrane lipid peroxidation, MDA content in tissues increases greatly under stress. 45 Compared with the single AsA treatment, the strawberry fruit treated with ceramide combined with AsA resulted in less MDA content, which suggested that ceramide could help to reduce the damage of the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Plants produce, like animals, the simple glycosphingolipid glucosylceramide (GlcCer) where glucose is β-linked to a phytoceramide that differs from animal ceramide in the composition of the sphingosine moiety [also referred as long-chain base (LCB)] (Spassieva and Hille, 2003;Pata et al, 2010;Ali et al, 2018;Huby et al, 2019). Another glycosylated sphingolipid in plants is glucosylinositol phosphoryl ceramide (GIPC) (Ali et al, 2018). Whereas in animals the major sphingosine base is C18 LCB, in plants over nine different LCBs have been identified.…”
Section: Sphingolipidsmentioning
confidence: 99%
“…Recently, a possible cause for the differences in the behaviour and localization of PDLP1 and PDLP5 has been identified [82]. Pd-lining plasma membrane is known to contain specific regions in which sphingolipids interact with sterols to create specialized domains [106,108,109], where GPI-anchored proteins accumulate [39,56]. Moreover, sphingolipid biosynthesis is very important for modulating Pd function [110].…”
Section: Plasmodesmata-located Protein 5 (Pdlp5)mentioning
confidence: 99%